Enzymatic Oxidation of Ca-Lignosulfonate and Kraft Lignin in Different Lignin-Laccase-Mediator-Systems and MDF Production - Euring, Markus; Ostendorf, Kolja; Rühl, Martin; Kües, Ursula (Frontiers in Bioengineering and Biotechnology, 2022)
Laccase-mediator-oxidized lignin offers replacement for conventional chemical binders to produce fiberboards. Compared to previously reported LMS (Laccase-Mediator-System), a Lignin-Laccase-Mediator-System (LLMS) has advantage that it requires much shorter fiber-enzyme incubation time due to significantly increased redox-reactions. However, the price of laccase for regular application on industrial scale is currently too high. We have employed CcLcc5 from cultures of the basidiomycete Coprinopsis cinerea as a novel basi-laccase (a CAZy subfamily AA1_1 laccase) in MDF (medium density fiberboard) production, in comparison to the commercial formulation Novozym 51003 with recombinantly produced asco-laccase MtL (a CAZy subfamily AA1_3 laccase-like multicopper oxidase from the ascomycete Myceliopthora thermophila). Using the best performing natural mediator DMP (2,6-dimethoxyphenol), unpurified CcLcc5 was almost as good as formulated Novozym 51003 in increasing the molecular weight (MW) of the technical lignins tested, the hydrophilic high-MW Ca-lignosulfonate and the hydrophobic low-MW kraft lignin (Indulin AT). Oxygen consumption rates of the two distantly related, poorly conserved enzymes (31% sequence identity) with different mediators and lignosulfonate were also comparable, but Indulin AT reduced significantly the oxidative activity of Novozym 51003 unlike CcLcc5 regardless of the mediator used, either DMP or guaiacol. Oxygen uptake by both laccases was much faster with both technical lignins with DMP than with guaiacol. In case of lignosulfonate and DMP, 20 to 30 minutes of incubation was sufficient for full oxygen consumption, which fits in well in time with the usual binder application steps in industrial MDF production processes. LLMS-bonded MDF was thus produced on a pilot-plant scale with either crude CcLcc5 or Novozym 51003 at reduced enzyme levels of 5 kU/kg absolutely dry wood fiber with lignosulfonate and mediator DMP. Boards produced with CcLcc5 were comparably good as those made with Novozym 51003. Boards reached nearly standard specifications in internal bond strength (IB) and modulus of rupture (MOR), while thickness swelling (TS) was less good based on the hydrophilic character of lignosulfonate. LLMS-bonded MDF with Indulin AT and DMP performed better in TS but showed reduced IB and MOR values.